Redes de cuidado e a assistência ofertada às crianças e adolescentes com transtorno do espectro autista em um município de médio porte - Bolatto, Nicole Bizarro (Universidade Federal de São Carlos, 2024)
Autism has been a present and prominent topic in the current context, especially in terms of concerns the care offered in the intra and intersectoral network, considering that the construction of public policies for this segment were implemented late. Given this, the objective of present study was to understand how assistance is given to children and adolescents with autism spectrum disorder in the intra and intersectoral care network of a city in medium size in the interior of the State of SP, from the perspective of those responsible or caregivers main. Five people responsible for autistic children and teenagers participated. The collection of data occurred in person and online, based on the choice of participants, being in On this occasion, a semi-structured interview guide was applied. The data was analyzed based on of content analysis. The results indicated that existing equipment is not sufficient for demand, so that family members wait for a long period of time to access diagnosis or treatment. However, they state about powers that touch on the bond established with professionals, the availability of even in welcoming and listening. It is also noteworthy that family members regularly access and have good links with basic health units and, in relation to schools, the The inclusion process involves barriers and challenges. Other network equipment as well have been activated by participants to guarantee rights, such as guardianship council and the specialized social assistance reference center. It is expected that the results obtained can contribute to further reflections on this topic, as well as to the qualification of the care offered
Care networks and assistance offered to children and adolescents with autism spectrum disorder in a medium-sized municipality
Keywords: Transtorno do espectro autista; Cuidado; Rede; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL